Representasi Budaya Jawa dalam Film “Lagi-Lagi Ateng” Karya Monty Tiwa serta Implementasinya sebagai Bahan Ajar BIPA Tingkat Mahir - Tiya Agustina (Badan Pengembangan dan Pembinaan Bahasa, 2021)
AbstractThere are many ways to improve the quality of BIPA institutions, one of which is through teaching materials. Films can be used as an alternative choice of media for delivering teaching materials in introducing language and culture to foreign students. This research is a qualitative descriptive study with a content analysis strategy in the film